(untitled) (International Journal of Physiotherapy, 2017)
Background: Physiotherapy is a form of rehabilitation science which helps to make a difference in an individual’s ability to live an active and healthy lifestyle. For many physiotherapists working in India, the primary source of reference is a physician. An aware physician can timely refer patients for physiotherapy who can in turn plan an effective management without making the rehabilitation journey taxing. This article will serve us to know about the interest and acceptance of physiotherapy and also to determine the extent of awareness among general practitioners. Methods: A sample size of 150 subjects were randomly chosen. The study was conducted in a questionnaire based interview format. All willing general practitioners from various streams along with super specialists were included, whereas interns and unwilling practitioners were excluded. Subjects were briefed about the study, written consent was taken before hand, and a validated questionnaire was personally given to fill in the details. The response thus obtained, was taken up for further analysis. Result: From the study, it was learned that there is awareness regarding physiotherapy among general practitioners. With regards to the different streams of physiotherapy, the Orthopedic (36%) and Neurological fields (24%) are the most popular, followed by Cardio respiratory (16%), Sports rehabilitation (14%) and only 6% aware of community-based rehabilitation. Conclusion: The study revealed that there is full awareness of physiotherapy among general practitioners. Musculoskeletal Physiotherapy showed good awareness among the study subjects. This was followed by NeuroPhysiotherapy, Cardio respiratory and Sports Physiotherapy. However, community-based rehabilitation was least known. Also, physicians believe that prescribing exercises is the main intervention used by a therapist and there is less information regarding the recent advances in rehabilitation.